US Geopolitical Grip on the Western Balkans: Spheres and Methods of Countering China’s Influence - Vankovska, Biljana (ВОПРОСЫ ПОЛИТОЛОГИИ, 2024)
The article examines the geopolitical influence of the United States and other Western powers on the countries of the Western Balkans (WB), as well as their strategies for countering China’s growing presence in the region. The central premise is that the Western Balkans have shifted from being a «near neighborhood» to a battleground of geopolitics and geo-economics. Until recently, the WB was taken for granted and treated as a loyal colony. However, significant changes have occurred both globally and internally. The decline of Western powers, driven by internal crises and overextended military hegemony, is increasingly evident. This decline is starkly contrasted by the remarkable economic, political, cultural, social, and technological growth of China and other non-Western countries, which have formed various mutual cooperation alliances. News of these developments has reached the EU’s periphery, prompting parts of Balkan societies, weary of interminable waits in the EU’s waiting halls, to seek alternatives. The process of gaining free access to objective information about non-Western advancements, particularly those in China, is ongoing but slow. In response, the Western hegemon resorts to propaganda and gaslighting, attempting to vilify Beijing, the Belt and Road Initiative (BRI), and the BRICS nations. The tentative conclusion is that populations in the Western Balkans are growing impatient and less willing to wait for the West’s promised «heaven on earth.» While the elites remain compliant and subservient, segments of society are exploring new paths to shape their own destiny in alignment with the Global Majority.
Keywords: West, US, China, Western Balkans, geopolitical influence